2020
DOI: 10.3389/fonc.2020.584793
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling Reveals Common and Specific Development Processes in Different Types of Gynecologic Cancers

Abstract: Background: Gynecologic cancers have become a major threat to women's health. The molecular biology of gynecologic cancers is not as well understood as that of breast cancer, and precision targeting is still new. Although viewed collectively as a group of cancers within the female reproductive system, they are more often studied separately. A comprehensive within-group comparison on molecular profiles is lacking.Methods: We conducted a whole-exome sequencing study of cervical/endometrial/ ovarian cancer sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Whole-exome sequencing has identified frequent molecular alterations along the HER2/PIK3/ AKT/mTOR pathway [26,27]. Zammataro et al identified genomic alterations in the oncogene PIK3CA or the PIK3CA pathway, including derangements in HER2 expression, in 52% of cervical tumors, primarily consisting of missense mutations and amplifications.…”
Section: Other Pathwaysmentioning
confidence: 99%
“…Whole-exome sequencing has identified frequent molecular alterations along the HER2/PIK3/ AKT/mTOR pathway [26,27]. Zammataro et al identified genomic alterations in the oncogene PIK3CA or the PIK3CA pathway, including derangements in HER2 expression, in 52% of cervical tumors, primarily consisting of missense mutations and amplifications.…”
Section: Other Pathwaysmentioning
confidence: 99%
“…To our knowledge, there existed several studies describing genomic features of Chinese cervical cancer patients, namely, cervical cancer cases of Chinese Hong Kong women (14), endocervical adenocarcinoma cases (15), 32 cervical cancer cases (16), 32 advanced cervical cancer (17), and 74 cervical cancer cases (18) of Chinese mainland women. However, the latter two studies focused on the molecular profiles of integrated gynecologic cancers containing ovarian cancer, endometrial cancer, and cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…CESC and UCEC are representative gynecological cancers. Although these two cancer types have different clinical features, origins, and prognoses, studies have demonstrated that gynecologic cancers share abnormally expressed genes [14]. Two hub genes Two positive risk coefficient genes (ITGB1, LDHA) in the lung group were related to amino acid transport.…”
Section: Discussionmentioning
confidence: 99%